If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 5) = 7(x + -7) Reorder the terms: 8(5 + x) = 7(x + -7) (5 * 8 + x * 8) = 7(x + -7) (40 + 8x) = 7(x + -7) Reorder the terms: 40 + 8x = 7(-7 + x) 40 + 8x = (-7 * 7 + x * 7) 40 + 8x = (-49 + 7x) Solving 40 + 8x = -49 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 40 + 8x + -7x = -49 + 7x + -7x Combine like terms: 8x + -7x = 1x 40 + 1x = -49 + 7x + -7x Combine like terms: 7x + -7x = 0 40 + 1x = -49 + 0 40 + 1x = -49 Add '-40' to each side of the equation. 40 + -40 + 1x = -49 + -40 Combine like terms: 40 + -40 = 0 0 + 1x = -49 + -40 1x = -49 + -40 Combine like terms: -49 + -40 = -89 1x = -89 Divide each side by '1'. x = -89 Simplifying x = -89
| x+8=4x+21 | | 2(4x-9)-6x=0 | | X*X-15X=0 | | 2-2w=26 | | x+8=4x+22 | | 3x-2=4x+10 | | 3-5a=42 | | -2(x+5)=-5x+3x+2 | | 5x+8=x+20 | | .25(4r-1)=2r+.125 | | 5(x-2)-4(x+1)=50 | | 2w=18 | | 0.35(x+6)=0.45(x+7) | | 9b=45 | | 3x+9=12x+16 | | 9b=6 | | 3(6+x)=2x | | 2(x+3)-2(x+4)=24 | | 3x+9=12x+6 | | x(.25)+12=x(.33)-5 | | 15x^4-25x^2+12x^2-20= | | 3x+9=3x+6 | | 3x+8=12x+6 | | 3x+8=3x+6 | | 6z=6 | | 3(4(.20)-.33)=12(.20)-1 | | x^2-35x-36=0 | | 9n^2-6n=3 | | 6c=6 | | -2(3y-1)-x=0 | | x^3=-10x^2-24x | | 24(y+2)=45 |